Dowry and Bride Price in Vietnam and Comparative Perspectives - Nguyen Thi My, Linh; Huynh Thi Truc, Giang (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Dowry and bride price are inherently two different types of property but have a close relationship through the marriage event between two individuals. This article is an analysis of the legal nature of these two assets under both the legal theory and practice. In terms of hypothesis, the law on marriage and family currently has enough legal bases to determine the general or specific nature of these two types of property, although it is not clearly mentioned in accordance with law. This study is also a comparison with countries’ regulations and analyses practical law application in Vietnam through judgments to bring a comprehensive view to the two different assets bearing the elements of marriage customs.